Government of Tajikistan Public Expenditure and Financial Accountability Assessment - World Bank; SWISSAID; U.K. Department for International Development (World Bank, Washington, DC, 2017)
Comparing this repeat Public Expenditure and Financial Accountability (PEFA) assessment with the original 2007 assessment reveals overall improvement across most Performance Indicators, with slippage in some areas and no change in rating for others. This 2012 PEFA report also takes place at a time of considerable transition as various PFM reforms are either newly implemented or in the process of being implemented and close to being implemented (e.g. a new chart of accounts; a new supreme audit act; adoption of the medium term expenditure framework and the implementation of a Public Financial Management (PFM) Reform Program). The purpose of the assessment is to assess the PFM system performance of the Government of Tajikistan, using the PEFA assessment methodology, and to gauge progress in strengthening performance since the last PEFA assessment conducted in 2007. The results of the assessment will principally be used by the Government to determine whether the Public Financial Management Economic Management Modernization Program (PFMMP) that it is currently implementing should be refined.